A Case Series of Waardenberg Syndrome - Alyscia Cheema, Nausheen Hayat (Pakistan Journal of Ophthalmology, 2018)
Waardenburg syndrome (WS) is a rare autosomally inherited and genetically heterogeneous disorder of neural crest cell development with distinct cutaneous manifestations1. We report here a case series of patients of a single family, presented with assemblage of complete heterochromia, dystopia canthorum, synophrys and broad nasal root. Other family members with presence of heterochromia and telecanthus have been delineated in pedigree. In our case series second generation of family also found to be affected, which is rarely reported till now. To our knowledge no local cases have been reported till date. Key words: Waardenberg syndrome, Heterochromia, Telecanthus.